Institutional Expenditures and Student Graduation and Retention - Dahlvig, Christopher A. (Christian higher education, 2020)
As the cost of higher education continues to rise faster than inflation and as the pressure from community colleges offering four-year degrees increases (See: https://www.pewtrusts.org/en/research-and-analysis/blogs/stateline/2018/04/26/more-community-colleges-are-offering-bachelors-degrees), it is imperative that colleges and universities examine how they allocate finite dollars in ways that increase retention and graduation rates. This study examined correlations between certain expense categories as defined by the Integrated Postsecondary Education Data System (IPEDS) and higher retention and six-year graduation rates of first-time, full-time students attending Council for Christian Colleges & Universities (CCCU) member institutions. The results of the hierarchical regression analysis suggest that the strongest correlations were dollars spent on instruction per full-time equivalent student being positively correlated to higher six-year graduation rates, and higher percentage of total spending used for research being positively correlated to higher retention rates.